Adopting a Tourist Perspective and Organizational Behavior to Strategically Improve Tourism Sustainability - Darwin Raja Unggul Saragih; Panca Purakusuma Idris; Sarfilianty Anggiani (Green Publisher Indonesia, 2024)
Tourism is a rapidly expanding global economic sector, contributing significantly to economic growth and social development. However, its expansion also poses challenges such as environmental degradation, socio-cultural disruptions, and economic inequalities. Sustainable tourism, which aims to balance economic, social, and environmental factors, is crucial for ensuring the long-term viability of the industry. This study explores the role of tourist perspectives, organizational behavior, and strategic management in promoting sustainable tourism, using Lake Toba, Indonesia, as a case study. A quantitative approach employing Structural Equation Modeling-Partial Least Squares (SEM-PLS) is used to analyze the relationships between these variables. Findings reveal that tourist perspectives, organizational behavior, and strategic management all significantly impact tourism sustainability. The research provides insights and practical recommendations for tourism destination managers and policymakers to develop strategies that align with sustainability principles, ultimately contributing to the long-term well-being of local communities and the environment.